Hairpin in a haystack: In silico identification and characterization of plant-conserved microRNA in Rafflesiaceae - Wicaksono Adhityo; Meitha Karlia; Wan Kiew-Lian; Mat Isa Mohd Noor; Parikesit Arli Aditya; Molina Jeanmaire (Open Life Sciences)
Rafflesiaceae is a family of endangered plants whose members are solely parasitic to the tropical grape vine Tetrastigma (Vitaceae). Currently, the genetics of their crosstalk with the host remains unexplored. In this study, we use homology-based in silico approaches to characterize micro-RNAs (miRNAs) expressed by Sapria himalayana and Rafflesia cantleyi from published omics data. Derived from secondary structures or hairpins, miRNAs are small regulators of gene expression. We found that some plant-conserved miRNA still exists in Rafflesiaceae. Out of 9 highly conserved miRNA families in plants, 7 families (156/157, 159/319, 160, 165/166, 171, 172, 390) were identified with a total of 22 variants across Rafflesiaceae. Some miRNAs were missing endogenous targets and may have evolved to target host miRNA, though this requires experimental verification. Rafflesiaceae miRNA promoters are mostly inducible by ethylene that mediates stress response in the host but could be perceived by the parasites as a signal for growth. This study provides evidence that certain miRNAs with ancient origins in land plants still exist in Rafflesiaceae, though some may have been coopted by parasites to target host genes.